The Meaning of Character Education in Citizenship Learning in Junior High Schools - Febby Azhura; Syarbaini Saleh (MASI Mandiri Edukasi, 2026)
This study aims to understand the meaning of character education in Civics Education (PKn) learning at MTs Laboratorium UIN Sumatera Utara (UINSU) and the role of teachers in shaping students' character. Character education is an important focus in the Merdeka Curriculum and in reinforcing Pancasila values to produce a generation that is virtuous, religious, and has a sense of nationalism. This study uses a qualitative case study design with PKn teachers and students in grades VII–IX as informants. Data were collected through in-depth interviews, participatory observation, and document analysis, and then analyzed using the interactive analysis techniques of Miles, Huberman, and Saldaña (2014), with source and method triangulation to ensure data validity. The research results show that character education in Civics at MTs Lab UINSU is implemented in an integrated manner through active learning, group discussions, case studies, and attitude assessments that emphasize discipline, responsibility, honesty, and respect for diversity. Civics teachers act as facilitators, mentors, and role models in instilling character values, supported by policies and a religious, conducive school environment. However, challenges such as differences in students' character readiness, limited access to technology, influences from the outside school environment, and limited learning time become obstacles to the optimal internalization of character.